Resistance and Change in West Kalimantan, The Kingdom of Sintang (1822-1942) - Suprianto, Bibi (Pascasarjana IAIN Pontianak, 2018)
Helius Sjamsuddin, Resistance and Change in West Kalimantan, The Kingdom of Sintang (1822-1942), Yogyakarta: Penerbit Ombak, 2015The presence of the book written by Helius Sjamsuddin shows the important of the studies of history in the academic atmosphere, not only global history but also local history in the studies of global history. By publishing the book entitled Resistance and Change in West Kalimantan THE KINGDOM OF SINTANG (1822-1942 the author tries to tell the world that such a remote area in the middle of the Borneo jungle has something very important to learn and share, the history of the Kingdom of Sintang in the context of Indonesian history of colonial time. The support by the Toyota Founation that the author got for the very important research project also indicates that the history of the Kingdom of Sintang has a significant influence in the Indonesian history, especially on the issue of resistance to the colonialism and social change within the Indonesian society. The author has provided a very interesting analysis and data collection supporting the book publication.